1987
DOI: 10.1038/330173a0
|View full text |Cite
|
Sign up to set email alerts
|

A new immunomodulating compound (AS-101) with potential therapeutic application

Abstract: There has been interest in the potential of synthetic compounds to modify immune responses by imitation of cytokine action. Direct administration of interleukin 2 (IL-2) in conjunction with adoptive transfer of lymphokine activated killer cells has been used in the treatment of cancer, but there are toxic effects resulting from the high doses of IL-2 required. We have developed a new synthetic compound, ammonium tri-chloro(dioxoethylene-O,O'-)tellurate (AS-101), which has immunomodulating properties and minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
115
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(119 citation statements)
references
References 1 publication
2
115
0
Order By: Relevance
“…This is further supported by the finding that AS101 increases GDNF production in rat glomerular mesangial cells (Kalechman et al, 2003) and GDNF mRNA levels in peripheral blood leukocytes and head kidney cells (Okun et al, 2006). AS101 is an immunomodulator (Sredni et al, 1987) that directly inhibits the transcription of IL-10 followed by the increase of specific cytokines including IL-1a and TNF-a (Sredni et al, 1987;Kalechman et al, 1995Kalechman et al, , 1997Strassmann et al, 1997). AS101 increases GDNF levels in rat astrocyte cultures and in the human SVG astrocyte cell line, while LPS-induced IL-10 secretion in the presence of AS101 is inhibited in both cell types (Sredni et al, 2007).…”
Section: Negative Regulation Of Gdnf Expressionsupporting
confidence: 68%
“…This is further supported by the finding that AS101 increases GDNF production in rat glomerular mesangial cells (Kalechman et al, 2003) and GDNF mRNA levels in peripheral blood leukocytes and head kidney cells (Okun et al, 2006). AS101 is an immunomodulator (Sredni et al, 1987) that directly inhibits the transcription of IL-10 followed by the increase of specific cytokines including IL-1a and TNF-a (Sredni et al, 1987;Kalechman et al, 1995Kalechman et al, , 1997Strassmann et al, 1997). AS101 increases GDNF levels in rat astrocyte cultures and in the human SVG astrocyte cell line, while LPS-induced IL-10 secretion in the presence of AS101 is inhibited in both cell types (Sredni et al, 2007).…”
Section: Negative Regulation Of Gdnf Expressionsupporting
confidence: 68%
“…Most of its activities have been primarily attributed to the direct inhibition of the anti-inflammatory cytokine interleukin (IL)-10 (15), followed by the simultaneous increase of specific cytokines (16 -18). These immunomodulatory properties were found to be crucial for the clinical activities of AS101, demonstrating the protective effects of AS101 in parasite-and virusinfected mice models (19), in autoimmune diseases (20), in septic mice (21), and in a variety of tumor models in mice and humans where AS101 had a clear antitumoral effect (16,22). Phase I clinical trials with advanced cancer patients treated with AS101 showed increased production and secretion of a variety of cytokines, leading to a clear dominance in TH1 responses with a concurrent decrease in the TH2 responses (22).…”
Section: Introductionmentioning
confidence: 99%
“…The most notable tellurium compound that exerts biological activity is found in the salt ammonium trichlorido (dioxyethylene-O,Oꞌ)tellurate, known as AS-101 ( Figure 1a) [25]. This low-molecular weight organotellurate is a potent immunomodulator [26] that has been in clinical trials for psoriasis [27], topical treatment for human papillomavirus [28], prevention of infertility in chemotherapy patients [29] and for inhibition of angiogenesis [24,30].…”
Section: Introductionmentioning
confidence: 99%